2019
DOI: 10.1016/j.supflu.2019.104607
|View full text |Cite
|
Sign up to set email alerts
|

Positioning supercritical solvolysis among innovative recycling and current waste management scenarios for carbon fiber reinforced plastics thanks to comparative life cycle assessment

Abstract: Global consumption of carbon fibers reinforced plastic (CFRP) is rising and the management of waste is an issue of high concern. In order to implement a sustainable carbon fiber recycling sector, there is a need to evaluate the potential environmental impacts of recycling processes. In this context, we compared current end-of-life scenarios (landfilling and incineration) with recycling technologies: pyrolysis, supercritical solvolysis and electrodynamic fragmentation using life cycle assessment. We conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 24 publications
(41 reference statements)
0
46
0
Order By: Relevance
“…For decades, the two most common disposal techniques used by the composite industry were landfill and incineration. The drawbacks of these techniques have led to increased environmental awareness, resulting in the search for sustainable disposal methods and strategies to avoid trash accumulation [33][34][35][36][37][38][39].…”
Section: Construction and Infrastructurementioning
confidence: 99%
“…For decades, the two most common disposal techniques used by the composite industry were landfill and incineration. The drawbacks of these techniques have led to increased environmental awareness, resulting in the search for sustainable disposal methods and strategies to avoid trash accumulation [33][34][35][36][37][38][39].…”
Section: Construction and Infrastructurementioning
confidence: 99%
“…Concern for the environment, limiting the utilization of finite resources, and the need to manage waste disposal, have led to increasing pressure to recycle materials at the end of their useful lives [ 23 ]. To ease the continued use of the composite material in some applications, such as wind turbine blades and the automotive industry (e.g., the BMW Group uses recycled carbon fibers for the manufacturing of the reinforcement of the C-pillar with sheet molding compound, and Toyota uses Mitsubishi Rayon’s sheet molding compound material for the manufacturing of the hatch door frame), it is crucial to modify composite waste into a valuable resource and close the loop within the composite life cycle [ 7 , 24 , 25 ]. Certainly, the enormous use of composite materials, thanks to their outstanding characteristics, leads to a rise in the quantity of waste produced.…”
Section: Difficulties With Composite Disposalmentioning
confidence: 99%
“…Overall, based on nine impact categories, the study concluded that pyrolysis possesses lower environmental and human health-based impacts compared with solvolysis to recycle CFRP wastes. Pillain et al (2019) [19] performed a comparative LCA study. They analysed the sustainability aspects and highlighted the advantages of recycling the CFRP wastes by solvolysis using SCW parallel to pyrolysis, electrodynamic fragmentation (mechanical recycling) and pointed out the disadvantages of traditional disposal methods such as incineration and landfill.…”
Section: Literature Reviewmentioning
confidence: 99%